Revision of the genus Delenda Croissandeau, 1891 (Coleoptera: Staphylinidae: Pselaphinae) - Bekchiev, Rostislav; Brachat, Volker (Zootaxa, 2014)
The genus Delenda Croissandeau, 1891 is revised and redescribed. The taxonomic position of the Delenda frivaldszkyi Reitter, 1893 is discussed, and its species status is resurrected. Delenda carthago Croissandeau, 1891, and D. frivaldszkyi Reitter, 1893 are redescribed. One new species D. rhodopensis sp. n. is described.